Implementasi Program Magang Merdeka Belajar di Desa - Lukman Pakaya; Ayu Rakhma Wuryandini (FKIP, Universitas Palangka Raya, 2024)
This internship activity aims to understand and implement village accounting knowledge obtained in college. This program is run as part of the PPKM Dikti grant program. The placement of this MBKM internship program is located in Ulantha Village, Suwawa District, Bone Bolango Regency. Ulantha Village was chosen because the village was a village that received a certificate awarded as the village with the third best financial management. This internship activity was carried out from August 19, 2022 to September 19, 2022. The basic methods used in this internship activity are the investigation stage, the provision stage, the implementation stage and finally the evaluation stage. In financial management in this application, it starts from planning, implementation, administration, reporting and accountability. The results of the internship practice showed that student participants were able to carry out the village financial management process well and until completion. This program is still expected to be carried out continuously as a provision for students to carry out work practices in the village.